ANALISIS KADAR SENYAWA FLAVONOID EKSTRAK ETANOL BUAH DENGEN (Dillenia serrata) MENGGUNAKAN SPEKTROFOTOMETER UV-VIS - Sukarti; Ilmiati Illing; Rini Rusman (Universitas Cokroaminoto Palopo)
Dengen fruit is one of the endemic fruit from South Sulawesi which is often found in the forest or in the yard of residents' houses. Dengen fruit contains flavonoid compounds that have the potential as medicine. Flavonoid compounds are known to have pharmacological activities such as antioxidant, anti-inflammatory, antibacterial, anticancer, antidiabetic, antihypertensive, etc. This study aims to determine the levels of flavonoid compounds from Dengen fruit extract using UV-Vis spectrophotometer method. The method in this study used fresh fruit extract without a thickening process using a rotary evaporator, then tested the levels of flavonoids using a UV-Vis spectrophotometer. The results of the research that have been carried out have obtained the flavonoid content of the Dengen fruit extract, which is 10.23 mg/mL or equivalent to 1.023%.